Cesarean scar pregnancy with deep serosal invasion at 16 weeks: Uterus‐sparing surgery with posterior hysterotomy after transcatheter arterial embolization. Issue 9 (5th July 2018) - Sroussi, Jérémy; Panchbhaya, Nabilah; Boujlel, Sihem; Dautry, Raphaël; Tigaizin, Ahmed; Benifla, Jean‐Louis
Abstract: We report a case of cesarean scar pregnancy at 16 weeks. Magnetic resonance imaging confirmed the isthmic ectopic location with an empty fundus and a high suspicion of placental invasion to the anterior myometrium. Because of pelvic pain, bleeding and the major risks of hysterectomy, a decision was made to terminate the pregnancy. After a preventive pelvic artery embolization, we performed an unusual posterior isthmic hysterotomy for the extraction of the fetus, followed by conservative management of the placenta. Bleeding loss was 300 mL, and no complication was reported. Successive magnetic resonance imaging was planned and 6 months later, there were no placental remnants. At 7 months, an office hysteroscopy revealed a normal uterine cavity. In case of cesarean scar pregnancy in the second trimester with an emergency need to interrupt pregnancy, posterior hysterotomy with conservative treatment of placenta may be an option to avoid massive bleeding and hysterectomy.